Optimization process of the truss structure using Finite Element Analysis: Step by step from 2D to 3D space - Arhami Arhami; Iskandar Hasanuddin; Masri Masri (Politeknik Negeri Lhokseumawe, 2023)
This paper discusses the process of optimizing the truss structure step by step from 2D to 3D space using finite element analysis. This step-by-step optimization process is carried out to simplify the analysis of truss structures from simple to more complex cases. Optimization aims to obtain the minimum cross-sectional area and weight for each truss member. The stages of the optimization process carried out in this study are starting from a 2-dimensional (2D) truss structure with several two and five members to a 3-dimensional (3D) one-level tower with a total of 18 members. The optimum criterion as the constraint used is the full stress design method and the value of the cross-sectional area and weight of the structure as a result of optimization, leading to convergence during the iteration process. The tool used to run the iteration process is performed using Fortran software. The results of this optimization process are the total cross-sectional area (A) and a minimum of weight (W), that is, for a two-member truss A = 1 in2 and W = 4 lb, for a five-member truss A = 3.48 in2 and W = 14 lb. Furthermore, for a one-level of tower-space truss with a total of 18 elements, A = 57.91 in2 is obtained and the optimum weight of the truss structure is W = 134.02 lb. From these results, it can be seen that the optimization process that starts from simple to complex cases can be carried out easily and still takes into account the existing constraints